Employee Training Efforts and Incentive Provision Towards Improving Employee Performance Through Customer Service at Kembar Ponsel Medan - Dea Aprillia Simamora; Barham Siregar; Nurul Dalimunte (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract This study was conducted to determine the efforts of employee training and providing incentives to improve employee performance through customer service at Kembar Ponsel Medan. The variables in this study consist of four independent variables, Job Training (X1) and Incentives (X2), while the dependent variable is Performance Improvement (Y) and the mediating variable is Service (Z). The research method used is a quantitative approach. Simultaneously, employee training efforts (X1) and providing incentives (X2) have a positive and significant influence on improving performance (Y). The combination of training that improves abilities and incentives that increase motivation is a very effective strategy to achieve optimal employee performance, namely the F-value (38,357) is greater than the F-table (3.34) with a significance value (0.000) less than 0.05. Simultaneously, employee training efforts (X1) and incentives (X2) have a positive and significant influence on customer service (Z), with the calculated F- value (11.326) greater than the F-table (3.34), and the significance value (0.000) less than 0.05. Thus, the synergy between increased capability (through training) and motivation (through incentives) results in higher service quality. Customer service (Z) is proven to act as an intervening variable that mediates the effect of incentives (X2) on performance improvement (Y). This means that incentives not only directly improve performance but also indirectly by motivating employees to provide better service, which ultimately improves performance. Keywords: Incentives, Performance, Service, Training.